Backshoring of production activities in European manufacturing. Issue 3 (June 2019) - Dachs, Bernhard; Kinkel, Steffen; Jäger, Angela; Palčič, Iztok
Abstract: Backshoring – the movement of manufacturing activities from locations abroad back to the home country – has gained some attention in policy discussions and in academic research in recent years. This paper presents empirical evidence on backshoring from a large sample of European manufacturing firms. The data indicate that backshoring is still uncommon among European firms. Around 4% of all firms in our sample have moved production back to the home country between 2013 and mid-2015. The most frequent reasons for backshoring are the loss of flexibility, a lack in quality of the goods produced abroad, and unemployed capacities at home. Flexibility and quality concerns are, in particular, relevant for firms that move production back from Asian countries. Backshoring is most likely for manufacturers of final products and in high-technology sectors, in particular in electrical equipment, information and communications equipment, and the Automotive industry. Highlights: There is one backshoring manufacturing firm for every three offshoring firms. Lower quality, flexibility and unemployed capacity are the main reasons for backshoring. Backshoring from Asia is more frequently driven by flexibility issues. High-technology sectors pursue flexible off- and backshoring strategies. Suppliers show lower backshoring propensity than manufacturers of final products.